Impact of changes in diabetes screening guidelines on testing eligibility and potential yield among adults without diagnosed diabetes in the United States. (March 2023) - Ali, Mohammed K.; Imperatore, Giuseppina; Benoit, Stephen R.; O'Brien, Matthew J.; Holliday, Christopher S.; Echouffo-Tcheugui, Justin B.; McKeever Bullard, Kai
Abstract: Aims: Recent USPSTF and ADA guidelines expanded criteria of whom to test to identify prediabetes and diabetes. We described which Americans are eligible and report receiving glucose testing by USPSTF 2015 and 2021 as well as ADA 2003 and 2022 recommendations, and performance of each guideline. Methods: We analyzed cross-sectional data from 6, 007 non-pregnant U.S. adults without diagnosed diabetes in the 2013–2018 National Health and Nutrition Examination Surveys. We reported proportions of adults who met each guideline's criteria for glucose testing and reported receiving glucose testing in the past three years, overall and by key population subgroups, . Defining prediabetes (FPG 100–125 mg/dL and/or HbA1c 5.7–6.4 %) or previously undiagnosed diabetes (FPG ≥ 126 mg/dL and/or HbA1c ≥ 6.5 %), we assessed sensitivity and specificity. Results: During 2013–2018, 76.7 million, 90.4 million, 157.7 million, and 169.5 million US adults met eligibility for glucose testing by USPSTF 2015, 2021, and ADA 2003 and 2022 guidelines, respectively. On average, 52 % of adults reported receiving glucose testing within the past 3 years. Likelihood of receiving glucose testing was lower among younger adults, men, Hispanic adults, those with less than high school completion, those living in poverty, and those without health insurance or a usual place of care than their respective counterparts. ADA recommendations were most sensitive (range: 91.0 % to 100.0 %) and least specific (range: 18.3 % to 35.3 %); USPSTF recommendations exhibited lower sensitivity (51.9 % to 66.6 %), but higher specificity (56.6 % to 74.5 %). Conclusions: An additional 12–14 million US adults are eligible for diabetes screening. USPSTF 2021 criteria provide balanced sensitivity and specificity while ADA 2022 criteria maximize sensitivity. Glucose testing does not align with guidelines and disparities remain.